A method for evaluating time‐resolved rheological functionalities of fluid foods. Issue 4 (24th April 2022) - Ohie, Kohei; Chiba, Haruko; Kumagai, Satomi; Yoshida, Taiki; Tasaka, Yuji
Abstract: We have developed an effective method for evaluating time‐resolved rheological functionalities of swallowed foods using ultrasonic spinning rheometry (USR). USR can obtain variations over time in the rheological properties of fluids despite the fluids being in heterogeneous and nonequilibrium conditions. In addition, USR can evaluate time variations of shear‐thinning property changing in a few seconds. Demonstrations were conducted with typical thickener solutions: starch, guar gum, and xanthan gum‐based solutions, with alpha‐amylase as a digestive enzyme. The flow curve of the starch‐based solutions lowered with time, and a few minutes after addition of the amylase, the viscosity dropped to one‐hundredth of the original value. In contrast, the guar gum‐ and xanthan gum‐based solutions maintained the original viscosities as generally known. Applying the power law fitting to series of these flow curves, the time variation of the shear‐thinning property is quantitatively characterized by the plots on typical K ‐ n space, where K and n are parameters in the model, consistency index and power law exponent. The qualitative characteristics of the thickeners are successfully quantified in the K ‐ n space, and this will be a practical tool for evaluating the time‐resolved rheological properties of swallowed foods. Abstract : Ultrasonic spinning rheometry described time variation of the instantaneous viscosity curves for typical thickener solutions with alpha‐amylase as a digestive enzyme. A K ‐ n diagram was constructed from the obtained viscosity curves for quantitatively characterizing time‐resolved rheological functionalities of fluid foods.